IMPACT OF COMPETENCE ON BUMDESMA SUSTAINABILITY: ORGANIZATIONAL COMMITMENT AS A MEDIATING VARIABLE - Surahmah, Daris (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study examines the relationship between competence, organizational commitment, and the sustainability of Joint Village-Owned Enterprises (BUMDESMA) in Jember Regency. Method: Using a quantitative explanatory research approach, data were collected from 104 core managers of 26 BUMDESMA through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. Results: The findings reveal that competence significantly influences both organizational commitment and BUMDESMA sustainability, with commitment serving as a critical mediating variable. The adjusted R² values demonstrate the robustness of the model, with competence explaining 49.1% of organizational commitment variation and competence and commitment together explaining 84.7% of sustainability variation. These results emphasize the importance of enhancing managerial skills and fostering organizational commitment through targeted training and leadership strategies to achieve long-term sustainability. Novelty: Practical implications suggest that policymakers should integrate competence development with initiatives to strengthen commitment and collaboration among stakeholders. Future research is recommended to explore additional factors, such as technological innovation and funding accessibility, to provide a more comprehensive understanding of BUMDESMA sustainability.